Identification of clinical and serological factors during induction treatment of lupus nephritis that are associated with renal outcome. Issue 1 (20th May 2015) - Dall'Era, Maria; Levesque, Victoria; Solomons, Neil; Truman, Matt; Wofsy, David
Abstract : Objective: To identify factors associated with clinical outcome in patients with lupus nephritis. Methods: Data from the Aspreva Lupus Management Study (ALMS) were analysed. Using multivariate analysis, we assessed the prognostic value of demographic, clinical, laboratory and histopathological features on the frequency of either complete remission (CR) or treatment failure (TF) during the maintenance phase. Results: Among the 370 subjects who entered the trial (complete population), non-Hispanic ethnicity was associated with a higher likelihood of CR (OR=2.0). Several factors were independently associated with a greater likelihood of TF, including: (1) anti-double-stranded DNA (anti-dsDNA) at trial entry (OR=12.7), (2) failure to reduce anti-dsDNA within 8 weeks (OR=2.9) and (3) failure to reduce urine protein:creatinine ratio (UP/C) by ≥25% within 8 weeks (OR=2.6). Among the 227 subjects who entered the maintenance phase (maintenance population), baseline estimated glomerular filtration rate (eGFR) ≥90 mL/min/1.73 m 2 was associated with a greater likelihood of CR (OR=2.0), and UP/C >1 at the end of induction was associated with a lower likelihood of CR (OR=0.3). Induction treatment with intravenous cyclophosphamide (IVC) was associated with a lower likelihood of TF (OR=0.5), while lack of treatment with antimalarials (OR=2.4), failure to reduce anti-dsDNA during the first 8 weeks of induction (OR=3.5), failure to reduce UP/C during the first 8 weeks of induction (OR=2.1) and anti-dsDNA positivity at the end of induction (OR=8.3) were independently associated with a greater likelihood of TF. Conclusions: This analysis demonstrates that levels of anti-dsDNA and UP/C during induction treatment are independently associated with renal outcome over the ensuing 3 years in both the complete and maintenance populations. Ethnicity is associated with renal outcome in just the complete population, and eGFR, induction treatment and treatment with antimalarials are associated with renal outcome in just the maintenance population.